The influence of social media marketing efforts towards brand perception of customers - Albutra, Angelie R.; Pornes, Natalia C; Almagro, Ronald E. (Journal of Sustainable Tourism and Entrepreneurship, 2023)
Purpose: This study investigates the relationship between social media marketing efforts and brand perception among customers of clothing stores in Davao del Norte, the Philippines. Research Methodology:  A descriptive-correlational research design was employed, involving 200 respondents selected through stratified sampling. Adapted questionnaires were used to measure social media marketing efforts and brand perception, and statistical analysis was conducted to determine the correlation. Results: The findings indicate a high level of social media marketing efforts, particularly in the areas of entertainment, interaction, trendiness, customization, and word-of-mouth. Functional perception has emerged as the most significant factor influencing brand perception. A significant correlation (p < 0.000, R = 0.784) was found between social media marketing efforts and brand perceptions. Limitations: The study's generalizability is limited because of its focus on a specific region and sample demographics. Contribution: This study underscores the critical role of social media marketing in fostering consumer trust and engagement in clothing stores. By leveraging user-generated content and entertainment elements, businesses can amplify brand visibility, deepen their emotional connections with customers, and foster loyalty and repeat purchases. Future research should delve deeper into the interplay between word-of-mouth marketing, affective perceptions, and brand identity to enrich our understanding of consumer behavior in the digital age.